PEMANFAATAN SUMBERDAYA HUTAN OLEH SUKU DAYAK MERATUS KALIMANTAN SELATAN - Arfa Agustina Rezekiah; Abdi Fithria; Adi Rahmadi (Lambung Mangkurat University-Indonesia, 2021)
Dayak Meratus in Loklahung Village, Loksado District, South Hulu Sungai Regency, South Kalimantan is one of the tribes living around the forest. They use forest resources to meet their daily needs. This research aims to analized the utilization of types and the forms of forest resources by indigenous peoples. Data collecting that used in this research are in-depth interviews and field observations. The analysis of data used tabulation matrix and qualitative description. The results showed that the utilization of forest resources is inherited from ancestors. The utilization of forest resources is mostly carried out in the forest in the form of activities: (1) Finding fuel and firewood; (2) Hunting; (3) Looking for handicraft materials; (4) Looking for nontimber forest products and (5). Looking for medicinal ingredients. The perception of dayak meratus people to the impact of forest resource utilization both flora and fauna belongs to the moderate category.